1968
DOI: 10.1172/jci105946
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of orthophosphate-32P into erythrocyte phospholipids in normal subjects and in patients with hereditary spherocytosis

Abstract: A B S T R A C T The in vitro incorporation of inorganic 32P into erythrocyte phospholipids has been studied in normal subjects and in splenectomized patients with hereditary spherocytosis (HS). Phosphatidic acid (PA) was the only lipid measurably labeled in both kinds of cells. The actual turnover rate of PA phosphate was determined by simultaneously isolating inorganic phosphate (PI) and adenosine triphosphate (ATP) and determining their specific activities. This turnover is very small: 1.3 ,umoles P/liter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1970
1970
1982
1982

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Incorporation of glycerides, glycerol, inorganic phosphorus, or cytidine diphosphate compounds were all minor in Release of Phospholipid Fatty Acid from Human Erythrocytes 1673 loo0 comparison to these two major incorporation routes (29,30). In other studies we have shown that for the active pathway the delivery of fatty acid from the plasma to the lysophosphatide acceptors within the cell proceeds through two discrete precursor pools (10).…”
Section: Discussionmentioning
confidence: 77%
“…Incorporation of glycerides, glycerol, inorganic phosphorus, or cytidine diphosphate compounds were all minor in Release of Phospholipid Fatty Acid from Human Erythrocytes 1673 loo0 comparison to these two major incorporation routes (29,30). In other studies we have shown that for the active pathway the delivery of fatty acid from the plasma to the lysophosphatide acceptors within the cell proceeds through two discrete precursor pools (10).…”
Section: Discussionmentioning
confidence: 77%
“…The membrane nature of the defect in HS was first suspected from the finding of an increased Na+ permeability in intact erythrocytes, an observation that has been shown consistently (Bertles, 1957;Jacob & Jandl, 1964;Wiley, 1972). Other membrane abnormalities have been described, such as an increased 32p turnover in the phospholipids (Reed, 1968), a reduction in the amount of membrane lipid per cell (Cooper & Jandl, 1969a) and decreased drug-induced endocytosis (Schrier et al, 1974). Despite these defects in membrane function, there have been no gross abnormalities detected with respect to membrane phospholipid distribution or fatty acid composition (de Gier et al , 1964; 0306-3275/82/020259-08$01.50/1 (© 1982 The Biochemical Society Robertson & Lands, 1964), although minor differences in the amounts of long-chain fatty acids in some phospholipid types have been claimed but not substantiated (Kuiper & Livne, 1972;Zail & Pickering, 1979).…”
mentioning
confidence: 99%
“…Ces resultats ont 6tB confirm& par Reed [7] demontrant une incorporation intense de [32P]orthophosphate dans les acides phosphatidiques, plus faible dans les phosphatidyls&ines, celle-ci Atant cependant accrue dans les hematies de malades atteints de sph6rocytose hereditaire et en rapport avec une augmentation du transfert du sodium.…”
unclassified